Malignant Peritoneal Mesothelioma as a Rare Cause of Dyspeptic Complaints and Ascites: A Diagnostic Challenge - Sousa,Susana Marques de (2020)
Introduction: Malignant peritoneal mesothelioma (MPM) is a rare malignancy of the mesothelial cells in the peritoneum. The best-defined risk factor is asbestos exposure, but germline mutations in BAP1 also increase susceptibility to this tumor. The diagnosis of MPM is challenging since clinical manifestations are often nonspecific. Case Presentation: We describe a case of MPM in a 53-year-old former construction worker with prior asbestos exposure. The clinical presentation was a 3-month history of dyspeptic complaints. As initial workup, abdominal ultrasound and upper gastrointestinal endoscopy were performed. Chronic gastritis due to Helicobacter pylori was detected, which was promptly treated but without symptom relief. Abdominal ultrasound showed small volume ascites with hyperechogenic foci, which was later confirmed on computed tomography scan showing the presence of peritoneal nodules in the greater omentum and mesentery. A thorough investigation was conducted based on the suspicion of peritoneal carcinomatosis. A non-peritoneal primary tumor was not found. Ascitic cytology and immunocytochemical studies were suggestive of mesothelioma. He underwent exploratory laparotomy and inoperable peritoneal disease was observed. Peritoneal biopsy confirmed epithelioid-type MPM. Systemic therapy was initiated with platinum plus pemetrexed with good response. The last follow-up was 38 months after the diagnosis. Discussion/ Conclusion: The diagnosis of MPM is challenging since it requires a high degree of suspicion. MPM has a poor prognosis. The standard of treatment recommended is cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. For those who are inoperable, systemic therapy with pemetrexed-cisplatin combination is the alternative. Given the infrequency of disease, it is imperative to ensure patient participation in clinical trials with the purpose of treatment standardization.